2022
DOI: 10.3389/fped.2022.974363
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of physical activity in children with bronchiectasis: Perspectives from children and parents

Abstract: BackgroundCurrent bronchiectasis management guidelines recommend regular physical activity but a large proportion of children with bronchiectasis do not meet public health recommendations which call for 60 min or more of moderate-to-vigorous intensity physical activity daily. Knowing the factors that influence physical activity in children with bronchiectasis is necessary for the development of effective interventions to increase physical activity in this patient group. The objective of this study was to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…The families’ preference for exercise programmes delivered locally is consistent with the results of a recent qualitative study that identified supportive physical activity environments as a facilitator of physical activity in children with bronchiectasis. 27 In this study, parents liked that the community venues were close to home or school, they felt that it was an accepted place where exercise occurs and appreciated the physical space inside the venues. Multiple systematic reviews highlight that physical environmental factors are consistently associated with physical activity.…”
Section: Discussionmentioning
confidence: 85%
“…The families’ preference for exercise programmes delivered locally is consistent with the results of a recent qualitative study that identified supportive physical activity environments as a facilitator of physical activity in children with bronchiectasis. 27 In this study, parents liked that the community venues were close to home or school, they felt that it was an accepted place where exercise occurs and appreciated the physical space inside the venues. Multiple systematic reviews highlight that physical environmental factors are consistently associated with physical activity.…”
Section: Discussionmentioning
confidence: 85%
“…The TDF contains 14 domains examining psychological (e.g., beliefs about capabilities, identity), social (e.g., social influences), and environmental (e.g., environmental context) influences on behaviour and has been utilised in qualitative research exploring children and adolescents’ physical activity. For example, the TDF has informed studies examining the barriers and facilitators to physical activity as perceived by children, parents and physical education teachers [ 46 , 47 ] and it has also been used to inform intervention development studies such as the design of a school-based intervention targeting adolescent girls [ 48 ]. This framework does not propose testable relationships between factors but provides a lens through which to view different influences on behaviour [ 49 ], thus, guiding analysis rather than imposing a predetermined structure [ 50 ].…”
Section: Introductionmentioning
confidence: 99%